Language attitude of undergraduate students towards English at English Education Department - Setyo Wati (LingTera, 2018)
This research aims to: (1) describe the language attitudes of undergraduate students of English Education Department of Surakarta Muhamamadiyah University toward English language in terms of their behavioural, cognitive, and affective aspects; and (2) investigate the differences in language attitudes of undergraduate students towards English across gender and length of study at English education department of Surakarta Muhammadiyah University. This research employed a mixed method research design to collect, analyse and to mix both quantitative and qualitative data in a single study. Researcher used theory in a quantitative study to provide an explanation about the relationship among variables in the study. Thus, it is essential to have grounding in the qualitative study. The results of the study are as follows. The undergraduate students have different language attitudes, in terms of cognitive, behavioural, and affective aspects of language attitudes towards English. There is a statistic difference in the undergraduate students’ language attitudes towards English across gender. The attitudes of male undergraduate students towards English are higher than that of female ones indicating more positive attitudes towards English. It means that there is a rejection of the null hypothesis, because there is a significant difference between male and female undergraduate students’ attitudes towards English. There is a difference among the three groups in terms of length of English study. The freshman group showed slightly higher language attitudes compared with those of the other two groups.